Decreases in inorganic nitrogen inputs and effects on nitrogen saturation and soil acidification. Issue 1 (2nd January 2020) - Baba, Mitsuhisa; Okazaki, Masanori; Matsuda, Kazuhide; Shima, Emu; Tachiyanagi, Fuka; Sugiura, Toshihiro; Toyota, Koki
ABSTRACT: We aimed to elucidate the effects of decreases in nitrogen (N) inputs on N budgets and soil acidity in N saturated forests in Tokyo, Japan using new analysis and comparison to sampling data collected in the 1990s. Canopy throughfall and soil-percolated water samples were collected from stands of Japanese cedar ( Cryptomeria japonica ) and Japanese cypress ( Chamaecyparis obtusa ), where allophanic Andisols have developed. Stream water was sampled at the outlet of the catchment (2.15 ha). The total inorganic N input due to throughfall in the Japanese cypress stand was 104–184 mmolc m −2 year −1, which is a marked decrease from sampling results from the 1990s (1991–1992 and 1995). This decrease can be ascribed to a reduction in NOx emission from automobiles. Consequently, nitrate (NO3 − ) outputs from the catchment decreased when compared with the previous study, although outputs were comparable to N inputs. Based on i) N budgets for the catchment and ii) episodic acidification of stream water, the study site remains N saturated. The degree of decrease in ammonium (NH4 + ) inputs was larger than NO3 − inputs, which resulted in a decrease in acid production due to nitrification or plant uptake and contributed to reduced soil acidification. As a result, the pH values of soil-percolated water in the Japanese cypress stand increased slightly, compared to levels in the 1990s. On the other hand, soil pH values in the Japanese cypress stand were comparable to those in the 1990s due to the large acid-neutralizing capacity of allophanic Andisols.